Sosialisasi pembuatan paving block cari limbah plastik berbasis pemberdayaan masyarakat di Kota Makassar - Syamfitriani Asnur; Arman Setiawan (DEDIKASI, 2020)
The Community Partnership Program (PKM) are people who are members of the Pabbata Ummi TPA Antang Foundation, which consists of Youth and Fathers groups and groups of mothers in RT 02 and 03 Tamangapa Village, Manggala District, Makassar City. The problem is: (1) constraints of knowledge and skills in processing plastic waste, especially for making paving blocks, (2) preparation of paving block manufacturing businesses. The external target is the use of plastic waste and technology that can turn it into a long-lived product so that it does not return to waste in a short time and has a high selling value so that it can improve the standard of living of citizens. The method used is: lectures, demonstrations, discussions, questions and answers, and counterpart partners. The results achieved are (1) partners have knowledge and skills in processing plastic waste, especially paving blocks, (2) partners have preparation to start a business making paving blocks.